2020
DOI: 10.1007/s10498-020-09376-w
|View full text |Cite|
|
Sign up to set email alerts
|

Ultra-trace Element Characterization of the Central Ottawa River Basin using a Rapid, Flexible, and Low-volume ICP-MS Method

Abstract: Ultra-trace (<1 ng g -1 ) rare earth elements and yttrium (REE+Y) and high field strength element (HFSE) geochemistry of freshwater can constrain element sources, aqueous processes in hydrologic catchments, and the signature of dissolved terrestrial fluxes to the oceans. This study details an adapted method capable of quantifying ≥38 elements (including all REE+Y, Nb, Ta, Zr, Hf, Mo, W, Th, U) with minimal sample preparation in natural water aliquots as low as ≤2 mL. The method precision and accuracy are demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 170 publications
(289 reference statements)
4
13
0
Order By: Relevance
“…Thus, accurate, precise, and reliable methods for their determination are a pre-requisite for interpreting the geochemical implications in environmental media such as river water, groundwater, and sea water. For example, Yeghicheyan et al (2019) and Babechuk et al (2020) reported compiled data for REE concentrations of SLRS-6 (natural river water certified reference material of NRC-CNRS). In the PAAS (Post-Archean Australian Shale)-normalized REE pattern, the shape of the HREE pattern shows some differences between these elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, accurate, precise, and reliable methods for their determination are a pre-requisite for interpreting the geochemical implications in environmental media such as river water, groundwater, and sea water. For example, Yeghicheyan et al (2019) and Babechuk et al (2020) reported compiled data for REE concentrations of SLRS-6 (natural river water certified reference material of NRC-CNRS). In the PAAS (Post-Archean Australian Shale)-normalized REE pattern, the shape of the HREE pattern shows some differences between these elements.…”
Section: Introductionmentioning
confidence: 99%
“…In the PAAS (Post-Archean Australian Shale)-normalized REE pattern, the shape of the HREE pattern shows some differences between these elements. In particular, the HREE pattern presented by Babechuk et al (2020) indicated the possibility of a specific pattern called the REE tetrad effect ( Peppard et al, 1969 ; Masuda and Ikeuchi, 1979 ; Masuda et al, 1987 ; Kawabe et al, 1998 ; Anenburg and Williams, 2022 ). However, the HREE pattern presented by Yeghicheyan et al (2019) shows a zigzag shape rather than the REE tetrad effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, weathering, redox, cation exchange process 3–5 ) and anthropogenic activities. 6–10 Analytical advances since the 1990s, particularly development and improvements of inductively coupled plasma-mass spectrometry (ICP-MS), have sparked the growing interest in low-abundance elements. 1 However, despite the outstanding merit of this analytical technique ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Therefore, the variations in the concentrations of these elements in the environment are commonly used to trace natural biogeochemical processes (e.g., weathering, redox, cation exchange process [3][4][5] ) and anthropogenic activities. [6][7][8][9][10] Analytical advances since the 1990s, particularly development and improvements of inductively coupled plasma-mass spectrometry (ICP-MS), have sparked the growing interest in lowabundance elements. 1 However, despite the outstanding merit of this analytical technique (e.g., low detection limits, large and linear dynamic range), spectral interferences (isobaric and polyatomic) represent the most signicant challenge to the method development workow, especially when there is a high ratio of interference-generating elements to analyte of interest.…”
Section: Introductionmentioning
confidence: 99%